Composite coating for battery diaphragm as well as preparation method and application of composite coating

Through innovative design of composite coating materials and water-based low-temperature preparation process, the technical bottlenecks of battery separator coatings in terms of high temperature resistance, ion conductivity, flame retardancy and interface compatibility have been solved, achieving safe, efficient and long-life performance of batteries, which are suitable for a variety of new energy batteries.

CN121108876AInactive Publication Date: 2025-12-12NINGBO YIKUI TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511297055.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-11
Publication Date
2025-12-12
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing battery separator coatings have technical bottlenecks in terms of high temperature resistance, ion conductivity, flame retardancy, interfacial compatibility, and preparation process, which cannot meet the requirements of new energy batteries for safety, efficiency, and long life. In particular, they have poor compatibility with solid electrolytes in the field of solid-state batteries, and traditional coating preparation processes are complex and have poor environmental performance.

Method used

A composite coating is formed through molecular-level reactions using components such as aminated graphene oxide-polydopamine grafts, polyimide-polyetheretherketone-nano SiO2 hybrids, hydroxyapatite-montmorillonite core-shell particles, zinc borate-melamine cyanurate composites, graphene quantum dots-carbon nanotube hybrids, and barium strontium titanate nanocrystals. This process constructs continuous ion conduction channels and flame-retardant networks, enhancing the overall performance of the coating. A water-based low-temperature preparation process is employed.

Benefits of technology

It significantly improves the battery's high temperature resistance and mechanical properties, enhances ionic conductivity, improves flame retardancy, improves interfacial compatibility, simplifies the manufacturing process, is suitable for various new energy battery systems, meets the needs of high-power batteries, and improves battery safety and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121108876A_ABST
    Figure CN121108876A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite coating preparation materials for battery diaphragms, in particular to a composite coating for a battery diaphragm as well as a preparation method and application. The invention discloses a graphene quantum dot / carbon nanotube composite material, which is prepared from the following components in percentage by weight: 3 to 8 percent of aminated graphene oxide-polydopamine graft, 10 to 18 percent of polyimide-polyetheretherketone-nano SiO2 hybrid, 2 to 5 percent of hydroxyapatite-montmorillonite core-shell particles, 0.5 to 3 percent of zinc borate-melamine cyanurate compound, 1 to 3 percent of graphene quantum dot-carbon nanotube hybrid, 2 to 6 percent of sodium carboxymethyl cellulose and 50 to 70 percent of deionized water. 0.5 to 2 percent of barium strontium titanate nanocrystalline or 1 to 3 percent of polyethylene glycol-polypropylene glycol segmented copolymer can also be added. All the components are combined through molecular-level reaction to construct a high-performance protection network. The composite coating is good in high temperature resistance and mechanical strength, high in ionic conduction efficiency, excellent in flame retardant effect and good in interfacial compatibility, the preparation process is environmentally friendly and easy to industrialize, the composite coating is suitable for various batteries, and the comprehensive performance of the composite coating is superior to that of a traditional coating.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of composite coating preparation for battery separators, in particular to a composite coating for battery separators and a preparation method and application thereof. BACKGROUND

[0002] With the development of new energy batteries towards high energy density and high power density, the performance of battery separators, as a key component, directly affects the safety, cycle stability and service life of the battery. Traditional battery separators are mostly made of polypropylene, polyethylene or their composite substrates. Although such substrates have good mechanical properties and ion permeability, they have two major defects: first, poor high temperature resistance, with PP separator thermal deformation temperature of about 160℃ and PE separator of about 130℃. When the battery generates local high temperature due to internal short circuit, overcharge and other problems, the separator is easy to melt, shrink and even break, leading to direct contact between the positive and negative electrodes and causing fire and explosion; second, weak resistance to electrolyte corrosion, which is easy to swell in long-term immersion in electrolyte, leading to damage of pore structure, increase of ion conduction impedance and attenuation of battery cycle performance.

[0003] To improve the performance of the separator, the existing technology mostly realizes modification by coating a functional coating. Common coating materials include ceramics, polymers and carbon materials. Ceramic coating can improve high temperature resistance, but has the problems of weak adhesion to the substrate and easy peeling of the coating, and the large gap between ceramic particles is easy to produce interface impedance after electrolyte immersion; polymer coating can enhance the adhesion to the substrate, but the ion conductivity of a single polymer is poor, and a large amount of plasticizer needs to be added, which reduces the mechanical strength of the coating; carbon material coating can improve ion conductivity, but carbon material is easy to agglomerate and lacks flame retardant function, which cannot solve the high temperature safety hazard of the battery.

[0004] In addition, the existing composite coating also has the problems of single function and poor synergy: some coatings only focus on high temperature resistance and ignore ion conduction efficiency, leading to a decrease in battery charge and discharge rate; some coatings consider both oxidation resistance and flame retardation, but use simple physical mixing, which lacks molecular-level interaction between components and is easy to cause stratification and sedimentation, affecting the stability of the coating. For example, in the traditional Al2O3-polyvinylidene fluoride composite coating, Al2O3 and polyvinylidene fluoride are only combined by van der Waals force, and Al2O3 particles are easy to fall off from the polyvinylidene fluoride matrix during the charge and discharge process of the battery, leading to failure of the separator performance; at the same time, the coating lacks ion conduction channel design, and the ion conductivity is only on the order of 10⁻ 4 S / cm, which cannot meet the needs of high-power batteries.

[0005] In the field of solid-state batteries, the existing coating also faces the problem of "poor compatibility with solid-state electrolyte": the interface impedance between the solid-state electrolyte and the traditional coating is high, and the coating cannot provide a continuous channel for ion transmission, resulting in increased battery resistance and rapid cycle performance degradation. In addition, sensitive skin and post-medical art skin have very high requirements for ingredient safety, and the preservatives (such as phenoxyethanol) and solvents (such as propylene glycol) commonly used in existing products may increase the burden on the skin, while preservative-free systems are difficult to balance long-term storage, further limiting the application scenarios of hydroxypropyl tetrahydropyran triol products.

[0006] At the same time, the existing coating preparation process is complex, such as ceramic coating which needs high-temperature sintering, high energy consumption and easy to cause substrate deformation; some polymer coatings need to use toxic solvents, which is poor in environmental protection. In summary, the existing battery separator coating has technical bottlenecks in high temperature resistance, ion conductivity, flame retardancy, interface compatibility and preparation process, and it is urgent to develop a new composite coating with multiple performance synergies, high stability and environmentally friendly preparation process to meet the needs of new energy batteries for safety, efficiency and long life. SUMMARY

[0007] (I) Technical problems solved In view of the deficiencies of the prior art, the present application provides a polypropylene conductive material and a preparation method thereof.

[0008] (II) Technical solutions A composite coating for battery separator, comprising the following components by weight percentage: amino-functionalized graphene oxide-polydopamine grafting material 3-8%, polyimide-polyether ether ketone-nano SiO2 hybrid 10-18%, hydroxyapatite-montmorillonite core-shell particles 2-5%, organosilane coupling agent KH-560 1-4%, zinc borate-melamine cyanurate complex 0.5-3%, graphene quantum dot-carbon nanotube hybrid 1-3%, sodium carboxymethyl cellulose 2-6%, and deionized water 50-70%.

[0009] The amino groups of the amino-functionalized graphene oxide NH2-GO react with the catechol groups of dopamine H2N-C6H3(OH)2 to form a Schiff base and a Michael addition reaction to form an amino-functionalized graphene oxide-polydopamine graft NH2-GO-PDA, and the reaction formula is NH2-GO+H2N-C6H3(OH)2→NH2-GO-PDA, and the polydopamine segment of the graft can enhance the interfacial bonding force with other components; the carboxyl groups of the polyimide-polyether ether ketone copolymer PI-PEEK react with the surface hydroxyl groups of nano-SiO2 to form a dehydration condensation reaction to form a polyimide-polyether ether ketone-nano-SiO2 hybrid PI-PEEK-SiO2, and the reaction formula is PI-PEEK-COOH+HO-SiO2→PI-PEEK-COO-SiO2+H2O, and the hybrid can improve the high-temperature resistance and mechanical strength of the coating; the hydroxyapatite-montmorillonite core-shell particles have montmorillonite as the core and hydroxyapatite as the shell, and the core-shell structure is constructed by a sol-gel method, and the shell layer hydroxyapatite can react with the epoxy groups of KH-560 to enhance the dispersibility of the particles in the coating; the zinc borate-melamine cyanurate complex is formed by hydrogen bonding, and can release a flame-retardant gas at high temperatures to synergistically improve the flame-retardant performance of the coating; the graphene quantum dot-carbon nanotube hybrid is combined by π-π stacking to construct a continuous ion conduction channel to improve the ion conductivity of the coating.

[0010] Further, it also includes 0.5-2% of barium strontium titanate nanocrystals. The barium strontium titanate nanocrystals are prepared by a hydrothermal synthesis method, using strontium nitrate, barium nitrate, and tetrabutyl titanate as raw materials, reacting at 180-220°C for 12-24 hours, and then washing by centrifugation, calcining at 600-800°C for 2-4 hours to obtain; the particle size is 10-30nm, the crystal structure is cubic perovskite type, the dielectric constant is 80-120, and the volume resistivity is ≥10 14 Ω·cm; the surface hydroxyl groups of the barium strontium titanate nanocrystals can form hydrogen bonds with the amino groups of the amino-functionalized graphene oxide-polydopamine graft, and are uniformly dispersed in the coating to form a synergistic ion conduction channel with the graphene quantum dot-carbon nanotube hybrid to reduce the ion transmission impedance.

[0011] Further, 1-3% of polyethylene glycol-polypropylene glycol block copolymer is further included. The polyethylene glycol-polypropylene glycol block copolymer is prepared by anionic polymerization of ethylene oxide and propylene oxide, the molecular weight of the polyethylene glycol segment is 1500-2500 g / mol, the molecular weight of the polypropylene glycol segment is 1500-2500 g / mol, the number average molecular weight is 3000-5000 g / mol; the hydrophilic-lipophilic balance is 8-12, and the viscosity at 25°C is 300-500 mPa·s; the ether bond of the block copolymer can form hydrogen bonds with the hydroxyl groups of sodium carboxymethyl cellulose, and the two end hydroxyl groups can react with the carboxyl groups of the polyimide-polyether ether ketone-nano SiO2 hybrid, thereby improving the interfacial bonding force of the coating and the separator substrate such as polypropylene and polyethylene, and reducing the peeling phenomenon of the coating during the charging and discharging process of the battery.

[0012] Further, the preparation process of the aminated graphene oxide-polydopamine graft is as follows: aminated graphene oxide and dopamine are added to Tris-HCl buffer solution at a mass ratio of 10:1-5:1, stirred at 200-300 rpm at 30-40°C for 6-12 hours, then ultrasonically dispersed at a power of 400-600 W and a frequency of 25-35 kHz for 40-80 minutes, and finally purified by dialysis to obtain the graft; the grafting rate of the graft is 15-25%, the sheet thickness is 0.8-2 nm, and the lateral size is 0.5-3 μm; the zeta potential in deionized water is -30 to -45 mV, and there is no obvious precipitation after standing for 72 hours, and the dispersion stability is excellent.

[0013] Further, the content of nano SiO2 in the polyimide-polyether ether ketone-nano SiO2 hybrid is 5-10% by mass fraction; the nano SiO2 is hydrophilic fumed silica with a particle size of 5-20 nm, a specific surface area of 200-300 m 2 / g, and a surface hydroxyl group density of 3-5 mmol / g; the preparation process of the hybrid is as follows: a polyimide-polyether ether ketone copolymer with a number average molecular weight of 60000-90000 g / mol and a carboxyl group content of 0.5-1.0 mmol / g is dissolved in N-methyl pyrrolidone, nano SiO2 is added, and stirring is carried out at 300-400 rpm at 60-80°C for 3-5 hours, during which the solution viscosity is measured every 1 hour, until the viscosity is stable; the thermal decomposition temperature of the hybrid is ≥500°C, the tensile strength is ≥80 MPa, and the solubility in N-methyl pyrrolidone is ≥30 g / 100 mL.

[0014] Further, the core-shell ratio of the hydroxyapatite-montmorillonite core-shell particle is 1:2-1:4; the montmorillonite is sodium-based montmorillonite, the particle size is 100-200 nm, the interlayer spacing is 1.2-1.5 nm, and the cation exchange capacity is 80-120 mmol / 100 g; the core-shell particle preparation process is: dispersing the montmorillonite in deionized water to prepare a suspension with a mass concentration of 2-5%, adding a calcium nitrate and diammonium hydrogen phosphate solution, adjusting the pH to 9.0-9.5, stirring at 200-300 rpm at 50-60°C for 4-6 hours, and then centrifuging, washing, and drying at 80-100°C to obtain the particle; the particle size is 50-150 nm, the specific surface area is 80-200 m 2 / g, and the surface hydroxyl density is 2.5-4.0 mmol / g.

[0015] Further, the mass ratio of the zinc borate-melamine cyanurate complex is 1:1-1:2; the zinc borate is of the type 2ZnO・3B2O3・3.5H2O, the particle size is 1-3 μm, the whiteness is ≥95%, and the water loss temperature is ≥300°C; the melamine cyanurate is a needle-shaped crystal, the particle size is 2-5 μm, and the decomposition temperature is ≥320°C; the complex preparation process is: adding the zinc borate and the melamine cyanurate into deionized water in proportion, stirring at 300-400 rpm at 30-40°C for 2-4 hours, and then spray drying (inlet air temperature 180-200°C, outlet air temperature 80-100°C) to obtain the complex; the decomposition temperature of the complex is ≥350°C (thermogravimetric analysis in air atmosphere), the limiting oxygen index is ≥30%, and after adding the complex to the coating, the vertical burning grade of the composite separator can reach V-0 level.

[0016] Further, a preparation method of a composite coating for a battery separator includes the following steps: S1. Prepare an amino-functionalized graphene oxide-polydopamine grafting dispersion: weigh the amino-functionalized graphene oxide and the dopamine in a mass ratio of 10:1-5:1, add a Tris-HCl buffer (pH 8.0-8.5), and control the solid-liquid ratio to be 1:20-1:30; add the mixture to a reaction kettle, stir at 200-300 rpm at 30-40°C for 6-12 hours; then transfer it to an ultrasonic device, ultrasonically disperse it at a power of 400-600 W and a frequency of 25-35 kHz for 40-80 minutes in an intermittent mode (work for 30 seconds and pause for 10 seconds); after ultrasonic treatment, put the dispersion into a dialysis bag with a molecular weight cutoff of 10,000 Da, dialyze it with deionized water for 24-48 hours, replace the deionized water 4-6 times during the period, and obtain the amino-functionalized graphene oxide-polydopamine grafting dispersion with a solid content of 5-10%.

[0017] S2. Preparation of polyimide-polyether ether ketone-nano SiO2 hybrid solution: weigh the polyimide-polyether ether ketone copolymer, add N-methyl pyrrolidone, control the solid-liquid ratio to be 1:5-1:8; stir at 300-400 rpm for 1-2 hours at 60-80°C until the copolymer is completely dissolved; add nano SiO2, continue to stir at 300-400 rpm for 3-5 hours at 60-80°C, and measure the solution viscosity every 1 hour during the stirring process by using a rotary viscometer until the viscosity change rate is ≤5%, to obtain a polyimide-polyether ether ketone-nano SiO2 hybrid solution, and the solid content is controlled to be 15-25%.

[0018] S3. Hydroxyapatite-montmorillonite core-shell particle treatment: weigh the hydroxyapatite-montmorillonite core-shell particles, add an ethanol-water mixed solvent, control the solid-liquid ratio to be 1:10-1:15; add silane coupling agent KH-550 (the amount is 3-5% of the mass of the core-shell particles), and stir at 200-300 rpm for 2-4 hours at 60-80°C; after the reaction, centrifugal separation is performed at a speed of 8000-10000 rpm for 10-15 minutes, the mixture is washed with ethanol for 3-4 times, and drying is performed at 80-100°C for 2-3 hours, to obtain modified hydroxyapatite-montmorillonite core-shell particles.

[0019] S4. Mixing reaction: mix the grafting dispersion prepared in S1 with the hybrid solution prepared in S2, adjust the stirring rate to be 400-600 rpm, and stir at 30-40°C for 1-2 hours; add silicone silane coupling agent KH-560 and the modified core-shell particles prepared in S3 according to 1-4% of the total mass of the coating, heat to 50-70°C, and continue to stir at 400-600 rpm for 2-3 hours, during which the mixed solution is sampled and observed every 30 minutes to ensure that there are no obvious particles.

[0020] S5. Functional component compounding and adjustment: add zinc borate-melamine cyanurate compound, graphene quantum dot-carbon nanotube hybrid, sodium carboxymethyl cellulose, and if the formula contains barium strontium titanate nanocrystals and polyethylene glycol-polypropylene glycol block copolymer, they are added together; stir at 300-400 rpm for 1-2 hours at 40-60°C, then transfer to an ultrasonic device, and perform ultrasonic dispersion at a power of 300-500 W and a frequency of 25-35 kHz for 30-60 minutes in pulse mode, working for 40 seconds and pausing for 15 seconds; after ultrasonic treatment, filter the mixed solution through a 0.2-0.5 μm polytetrafluoroethylene filter membrane to remove undispersed large particles; measure the solid content of the filtered mixed solution, if the solid content is higher than 35%, add deionized water for dilution, if the solid content is lower than 20%, perform vacuum concentration at 40-50°C and a vacuum degree of 0.08-0.1 MPa, and finally adjust the solid content to be 20-35%, to obtain a composite coating slurry for battery separators.

[0021] Furthermore, the amino loading of the aminated graphene oxide in S1 needs to be pre-determined by potentiometric titration to ensure it is 1.2-1.8 mmol / g. If the loading is insufficient, the amination process needs to be repeated. In S2, N-methylpyrrolidone needs to be dehydrated by molecular sieve, with the moisture content controlled to ≤0.1% to avoid affecting the formation of hybrids. In S4, KH-560 needs to be purified by vacuum distillation before use to remove low-boiling-point impurities. The distillation temperature is 180-190℃ and the vacuum degree is 0.09-0.1MPa. In S5, the ultrasonic dispersion process needs to control the system temperature to ≤60℃ by a constant temperature water bath to avoid high temperature causing the aggregation of barium strontium titanate nanocrystals or the decomposition of polyethylene glycol-polypropylene glycol block copolymers. After filtration, the viscosity of the coating slurry needs to be measured by a rotational viscometer. The viscosity needs to be controlled to 1000-3000 mPa·s at 25℃. If the viscosity does not meet the requirements, it can be adjusted by adjusting the solid content or adding sodium carboxymethyl cellulose.

[0022] Furthermore, this composite coating is used for membrane coating in solid-state lithium-ion batteries, sodium-ion batteries, or potassium-ion batteries. Suitable substrate membranes include polypropylene membranes, polyethylene membranes, and polypropylene-polyethylene-polypropylene three-layer composite membranes. Before coating, the substrate membrane needs to undergo plasma pretreatment with a power of 100-200W for 1-3 minutes using argon gas to improve surface roughness and hydrophilicity. Coating methods include blade coating, microgravure coating, or spraying. For blade coating, the blade gap is controlled to be 5-20μm. The coating speed is 1-3 m / min; the anilox roller for microgravure coating has a mesh count of 200-400 and a coating speed of 2-5 m / min; the nozzle diameter for spraying is 0.2-0.5 mm, the spraying pressure is 0.1-0.3 MPa, and the spraying distance is 10-20 cm; after coating, the diaphragm is placed in an oven and dried at 80-120℃ for 1-3 hours, followed by hot pressing at 120-160℃ and 5-10 MPa for 0.5-2 hours to produce a composite diaphragm; the ionic conductivity of this composite diaphragm is ≥1.0×10⁻ 3 With a heat shrinkage rate of ≤5% at 150℃ and a puncture strength of ≥1500g, it can improve the cycle stability and safety performance of the battery.

[0023] (iii) Beneficial technical effects Compared with existing technologies, the beneficial effects of this invention are: In terms of high temperature resistance and mechanical properties, this invention constructs a coating framework through a polyimide-polyetheretherketone-nano SiO2 hybrid. In the hybrid, the nano SiO2 forms covalent bonds with the polymer matrix, which greatly improves the thermal stability of the coating and avoids the problem of high-temperature melting and shrinkage of traditional coatings. At the same time, the sheet-like structure of the aminated graphene oxide-polydopamine graft can form a support network in the coating, enhance the mechanical strength of the coating, reduce the damage to the coating caused by vibration and extrusion during battery cycling, and extend the service life of the separator.

[0024] In terms of ion conduction performance, this invention innovatively constructs a synergistic ion channel of "graphene quantum dot-carbon nanotube hybrid + barium strontium titanate nanocrystals": the graphene quantum dot-carbon nanotube hybrid forms a continuous conductive network through π-π stacking, and the high dielectric constant of barium strontium titanate nanocrystals can reduce the activation energy of ion transport. The two work together to improve the ion conductivity of the coating, solve the problem of high ion conduction impedance of traditional coatings, and significantly improve the battery charge and discharge rate to meet the requirements of high-power batteries.

[0025] In terms of flame retardancy and safety performance, this invention employs a zinc borate-melamine cyanurate composite and hydroxyapatite-montmorillonite core-shell particles for synergistic flame retardancy: the composite releases flame-retardant gases at high temperatures to inhibit combustion, the montmorillonite core of the core-shell particles can form a flame-retardant barrier, and the hydroxyapatite shell can adsorb electrolyte decomposition products. The combination of the two significantly improves the flame retardant effect of the coating, avoids the risk of battery short circuit fire, significantly improves battery safety performance, and solves the defect of traditional coatings lacking an effective flame retardant mechanism.

[0026] Regarding interfacial compatibility, this invention improves the interfacial bonding between the coating and the substrate and electrolyte through polyethylene glycol-polypropylene glycol block copolymers: the hydrophilic segments of the block copolymer can enhance the wettability of the coating and the electrolyte, while the hydrophobic segments can improve the bonding force with polypropylene and polyethylene substrates, reduce coating peeling and interfacial impedance, and are especially suitable for solid electrolytes of solid-state batteries, reducing the probability of interfacial reaction and improving battery cycle stability.

[0027] In terms of preparation process and environmental protection, this invention adopts a water-based system and low-temperature preparation process, avoiding the problems of high-temperature sintering or toxic solvents used in traditional coatings, thus reducing energy consumption and environmental protection costs. At the same time, the components are combined through molecular-level reactions, resulting in excellent dispersion stability. Uniform coating can be achieved without complex post-treatment. The process is simple and easy to industrialize, making it suitable for large-scale production.

[0028] Furthermore, the coating of this invention is compatible with various systems such as lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries, and can meet the performance requirements of different batteries by adjusting the component ratio. It has a wide range of applications and its comprehensive performance is superior to existing separator coatings, providing key technical support for the safe and efficient development of new energy batteries. Attached Figure Description

[0029] Figure 1 This is a flowchart of a composite coating for battery separators and its preparation method proposed in this invention; Figure 2 This is a line graph showing the change in ionic conductivity of the composite diaphragm before and after immersion in the electrolyte. Figure 3 It is a bar chart showing the tensile strength and elongation at break of the composite diaphragm. Figure 4This is a bar chart showing the uniformity of the composite coating at different coating speeds. Detailed Implementation

[0030] according to Figures 1 to 4 The specific embodiments of the present invention are as follows: A composite coating for battery separators comprises the following components by weight percentage: 3-8% aminated graphene oxide-polydopamine graft, 10-18% polyimide-polyetheretherketone-nano SiO2 hybrid, 2-5% hydroxyapatite-montmorillonite core-shell particles, 1-4% organosilane coupling agent KH-560, 0.5-3% zinc borate-melamine cyanurate composite, 1-3% graphene quantum dot-carbon nanotube hybrid, 2-6% sodium carboxymethyl cellulose, and 50-70% deionized water.

[0031] The amino groups of aminated graphene oxide (NH2-GO) undergo a Schiff base reaction and Michael addition reaction with the catechol groups of dopamine (H2N-C6H3(OH)2) to form the aminated graphene oxide-polydopamine graft NH2-GO-PDA, with the reaction formula NH2-GO + H2N-C6H3(OH)2 → NH2-GO-PDA. The polydopamine segments of the graft enhance the interfacial bonding with other components. The carboxyl groups of the polyimide-polyetheretherketone copolymer (PI-PEEK) undergo a dehydration condensation reaction with the hydroxyl groups on the surface of nano-SiO2 to form the polyimide-polyetheretherketone-nano-SiO2 hybrid PI-PEEK-SiO2, with the reaction formula PI- The hybrid structure PEEK-COOH+HO-SiO2→PI-PEEK-COO-SiO2+H2O enhances the high-temperature resistance and mechanical strength of the coating. Hydroxyapatite-montmorillonite core-shell particles, with montmorillonite as the core and hydroxyapatite as the shell, are constructed using a sol-gel method to create a core-shell structure. The hydroxyapatite shell reacts with the epoxy groups of KH-560, enhancing the dispersion of particles in the coating. The zinc borate-melamine cyanurate composite is formed through hydrogen bonding, releasing flame-retardant gases at high temperatures and synergistically improving the flame-retardant properties of the coating. The graphene quantum dot-carbon nanotube hybrid is bound together through π-π stacking interactions, constructing continuous ion conduction channels and improving the ionic conductivity of the coating.

[0032] Furthermore, it also includes 0.5-2% barium strontium titanate nanocrystals. Barium strontium titanate nanocrystals are prepared by hydrothermal synthesis using strontium nitrate, barium nitrate, and tetrabutyl titanate as raw materials. The reaction is carried out at 180-220℃ for 12-24 hours, followed by centrifugal washing and calcination at 600-800℃ for 2-4 hours. The nanocrystals have a particle size of 10-30 nm, a cubic perovskite crystal structure, a dielectric constant of 80-120, and a volume resistivity ≥10⁻⁶. 14Ω・cm; The surface hydroxyl groups of barium strontium titanate nanocrystals can form hydrogen bonds with the amino groups of aminated graphene oxide-polydopamine grafts, and are uniformly dispersed in the coating. They form synergistic ion conduction channels with graphene quantum dots-carbon nanotube hybrids, reducing ion transport impedance.

[0033] Furthermore, it also includes 1-3% polyethylene glycol-polypropylene glycol block copolymer. The polyethylene glycol-polypropylene glycol block copolymer is prepared by anionic polymerization of ethylene oxide and propylene oxide. The molecular weight of the polyethylene glycol segments is 1500-2500 g / mol, the molecular weight of the polypropylene glycol segments is 1500-2500 g / mol, and the number average molecular weight is 3000-5000 g / mol. Its hydrophilic-lipophilic balance value is 8-12, and its viscosity at 25℃ is 300-500 mPa·s. The ether bonds of this block copolymer can form hydrogen bonds with the hydroxyl groups of sodium carboxymethyl cellulose, and its two hydroxyl groups can react with the carboxyl groups of the polyimide-polyetheretherketone-nano SiO2 hybrid, improving the interfacial adhesion between the coating and the polypropylene, polyethylene, and other separator substrates, and reducing coating peeling during battery charging and discharging.

[0034] Furthermore, the preparation process of the aminated graphene oxide-polydopamine graft is as follows: aminated graphene oxide and dopamine are added to Tris-HCl buffer at a mass ratio of 10:1-5:1, stirred at 200-300 rpm for 6-12 hours at 30-40℃, and then ultrasonically dispersed at 400-600W power and 25-35kHz frequency for 40-80 minutes. After purification by dialysis, the graft has a grafting rate of 15-25%, a sheet thickness of 0.8-2nm, and a lateral size of 0.5-3μm. The zeta potential in deionized water is -30 to -45mV, and no obvious precipitation is observed after standing for 72 hours, indicating excellent dispersion stability.

[0035] Furthermore, the polyimide-polyetheretherketone-nano SiO2 hybrid contains 5-10% by mass of nano-SiO2; the nano-SiO2 is hydrophilic fumed silica with a particle size of 5-20 nm and a specific surface area of ​​200-300 m² / g. 2 / g, surface hydroxyl density 3-5mmol / g; the hybrid preparation process is as follows: dissolve polyimide-polyetheretherketone copolymer with a number average molecular weight of 60000-90000g / mol and a carboxyl content of 0.5-1.0mmol / g in N-methylpyrrolidone, add nano SiO2, stir at 300-400rpm for 3-5 hours at 60-80℃, and take samples every 1 hour to measure the viscosity of the solution until the viscosity is stable; the thermal decomposition temperature of the hybrid is ≥500℃, the tensile strength is ≥80MPa, and the solubility in N-methylpyrrolidone is ≥30g / 100mL.

[0036] Furthermore, the core-shell ratio of the hydroxyapatite-montmorillonite core-shell particles is 1:2-1:4; the montmorillonite is sodium-based montmorillonite with a particle size of 100-200 nm, an interlayer spacing of 1.2-1.5 nm, and a cation exchange capacity of 80-120 mmol / 100 g; the preparation process of the core-shell particles is as follows: montmorillonite is dispersed in deionized water to prepare a suspension with a mass concentration of 2-5%, calcium nitrate and diammonium hydrogen phosphate solution is added, the pH is adjusted to 9.0-9.5, and the mixture is stirred at 200-300 rpm for 4-6 hours at 50-60℃. After centrifugation, washing, and drying at 80-100℃, the particles are obtained; the particle size is 50-150 nm, and the specific surface area is 80-200 m² / g. 2 / g, surface hydroxyl density 2.5-4.0mmol / g.

[0037] Furthermore, the mass ratio of the zinc borate-melamine cyanurate composite is 1:1-1:2; the zinc borate is of the 2ZnO・3B2O3・3.5H2O type, with a particle size of 1-3μm, whiteness ≥95%, and dehydration temperature ≥300℃; the melamine cyanurate is a needle-like crystal with a particle size of 2-5μm and a decomposition temperature ≥320℃; the composite is prepared by adding zinc borate and melamine cyanurate to deionized water in a certain proportion, stirring at 300-400rpm for 2-4 hours at 30-40℃, and then spray drying (inlet air temperature 180-200℃, outlet air temperature 80-100℃); the composite has a decomposition temperature ≥350℃ (thermogravimetric analysis, air atmosphere), a limiting oxygen index ≥30%, and when added to the coating, it can make the vertical combustion rating of the composite membrane reach V-0 level.

[0038] Furthermore, a method for preparing a composite coating for a battery separator includes the following steps: S1. Preparation of aminated graphene oxide-polydopamine graft dispersion: Weigh aminated graphene oxide and dopamine at a mass ratio of 10:1-5:1, add Tris-HCl buffer (pH 8.0-8.5), and control the solid-liquid ratio at 1:20-1:30; add the mixture to a reaction vessel and stir at 200-300 rpm for 6-12 hours at 30-40℃; then transfer to an ultrasonic device and sonicate at 400-600W power and 25-35kHz frequency for 40-80 minutes (using intermittent mode, working for 30 seconds and pausing for 10 seconds). After sonication, put the dispersion into a dialysis bag, retain a molecular weight cutoff of 10000 Da, and dialyze with deionized water for 24-48 hours, changing the deionized water 4-6 times during the period to obtain an aminated graphene oxide-polydopamine graft dispersion with a solid content controlled at 5-10%.

[0039] S2. Preparation of polyimide-polyetheretherketone-nano SiO2 hybrid solution: Weigh the polyimide-polyetheretherketone copolymer, add N-methylpyrrolidone, and control the solid-liquid ratio at 1:5-1:8; stir at 300-400 rpm for 1-2 hours at 60-80℃ until the copolymer is completely dissolved; add nano SiO2, and continue stirring at 300-400 rpm for 3-5 hours at 60-80℃, measuring the viscosity of the solution every hour during this period with a rotational viscometer until the viscosity change rate is ≤5%, to obtain the polyimide-polyetheretherketone-nano SiO2 hybrid solution, with the solid content controlled at 15-25%.

[0040] S3. Treatment of hydroxyapatite-montmorillonite core-shell particles: Weigh hydroxyapatite-montmorillonite core-shell particles, add ethanol-water mixed solvent, and control the solid-liquid ratio at 1:10-1:15; add silane coupling agent KH-550 (3-5% of the mass of the core-shell particles), and stir at 200-300 rpm for 2-4 hours at 60-80℃; after the reaction, centrifuge at 8000-10000 rpm for 10-15 minutes, wash with ethanol 3-4 times, and dry at 80-100℃ for 2-3 hours to obtain modified hydroxyapatite-montmorillonite core-shell particles.

[0041] S4. Mixing reaction: Mix the graft dispersion prepared in S1 with the hybrid solution prepared in S2, adjust the stirring speed to 400-600 rpm, and stir at 30-40℃ for 1-2 hours; add organosilane coupling agent KH-560 and modified core-shell particles prepared in S3 at 1-4% of the total mass of the coating, heat to 50-70℃, and continue stirring at 400-600 rpm for 2-3 hours. During this period, take samples every 30 minutes to observe the state of the mixture to ensure that there are no obvious particles.

[0042] S5. Functional Component Composition and Adjustment: Add zinc borate-melamine cyanurate composite, graphene quantum dot-carbon nanotube hybrid, and sodium carboxymethyl cellulose. If the formulation contains barium strontium titanate nanocrystals and polyethylene glycol-polypropylene glycol block copolymer, add them together. Stir at 300-400 rpm for 1-2 hours at 40-60℃, then transfer to an ultrasonic device and ultrasonically disperse at 300-500W power and 25-35kHz frequency for 30-60 minutes using pulse mode, working for 40 seconds and pausing for 15 seconds. After ultrasonication, filter the mixture through a 0.2-0.5μm polytetrafluoroethylene filter membrane to remove undispersed large particles. Measure the solid content of the filtered mixture. If the solid content is higher than 35%, dilute with deionized water. If it is lower than 20%, concentrate under reduced pressure at 40-50℃ and 0.08-0.1MPa vacuum. Finally, adjust the solid content to 20-35% to obtain the composite coating slurry for battery separators.

[0043] Furthermore, the amino loading of the aminated graphene oxide in S1 needs to be pre-determined by potentiometric titration to ensure it is 1.2-1.8 mmol / g. If the loading is insufficient, the amination process needs to be repeated. In S2, N-methylpyrrolidone needs to be dehydrated by molecular sieve, with the moisture content controlled to ≤0.1% to avoid affecting the formation of hybrids. In S4, KH-560 needs to be purified by vacuum distillation before use to remove low-boiling-point impurities. The distillation temperature is 180-190℃ and the vacuum degree is 0.09-0.1MPa. In S5, the ultrasonic dispersion process needs to control the system temperature to ≤60℃ by a constant temperature water bath to avoid high temperature causing the aggregation of barium strontium titanate nanocrystals or the decomposition of polyethylene glycol-polypropylene glycol block copolymers. After filtration, the viscosity of the coating slurry needs to be measured by a rotational viscometer. The viscosity needs to be controlled to 1000-3000 mPa·s at 25℃. If the viscosity does not meet the requirements, it can be adjusted by adjusting the solid content or adding sodium carboxymethyl cellulose.

[0044] Furthermore, this composite coating is used for membrane coating in solid-state lithium-ion batteries, sodium-ion batteries, or potassium-ion batteries. Suitable substrate membranes include polypropylene membranes, polyethylene membranes, and polypropylene-polyethylene-polypropylene three-layer composite membranes. Before coating, the substrate membrane needs to undergo plasma pretreatment with a power of 100-200W for 1-3 minutes using argon gas to improve surface roughness and hydrophilicity. Coating methods include blade coating, microgravure coating, or spraying. For blade coating, the blade gap is controlled to be 5-20μm. The coating speed is 1-3 m / min; the anilox roller for microgravure coating has a mesh count of 200-400 and a coating speed of 2-5 m / min; the nozzle diameter for spraying is 0.2-0.5 mm, the spraying pressure is 0.1-0.3 MPa, and the spraying distance is 10-20 cm; after coating, the diaphragm is placed in an oven and dried at 80-120℃ for 1-3 hours, followed by hot pressing at 120-160℃ and 5-10 MPa for 0.5-2 hours to produce a composite diaphragm; the ionic conductivity of this composite diaphragm is ≥1.0×10⁻ 3 With a heat shrinkage rate of ≤5% at 150℃ and a puncture strength of ≥1500g, it can improve the cycle stability and safety performance of the battery.

[0045] The following three examples and one comparative example illustrate in detail the selection of raw materials, formulation composition, preparation process and performance testing of the composite coating for battery separators described in this patent. The content of each component is expressed as a weight percentage, and all raw materials used meet the requirements of industrial-grade purity. The performance testing methods are performed in accordance with the battery separator industry standards.

[0046] Example 1 Raw material preparation and parameters: Aminated graphene oxide-polydopamine graft: grafting rate 15%, sheet thickness 0.8 nm, lateral dimension 0.5 μm, zeta potential -30 mV, aqueous dispersion with 5% solid content, dialysis cutoff molecular weight 10000 Da during preparation, dialysis time 24 hours.

[0047] Polyimide-polyetheretherketone-nano SiO2 hybrid: 5% nano SiO2 content, 5nm nano SiO2 particle size, 200m² specific surface area. 2 / g, surface hydroxyl density 3mmol / g; hybrid thermal decomposition temperature 500℃, tensile strength 80MPa, number average molecular weight 60000g / mol, N-methylpyrrolidone solution with 15% solid content, N-methylpyrrolidone moisture content 0.1%.

[0048] Hydroxyapatite-montmorillonite core-shell particles: core-shell ratio 1:2, particle size 50 nm, specific surface area 80 m² 2 / g, surface hydroxyl density 2.5mmol / g; montmorillonite is sodium-based montmorillonite, cation exchange capacity 80mmol / 100g; modified with silane coupling agent KH-550, modification temperature 60℃, modification time 2 hours, KH-550 dosage is 3% of the mass of core-shell particles.

[0049] Zinc borate-melamine cyanurate complex: mass ratio 1:1, particle size 1μm, whiteness 95%, decomposition temperature 350℃, limiting oxygen index 30%; zinc borate is of the 2ZnO・3B2O3・3.5H2O type, with a dehydration temperature of 300℃; melamine cyanurate is a needle-like crystal with a decomposition temperature of 320℃.

[0050] Graphene quantum dot-carbon nanotube hybrid: The graphene quantum dots have a particle size of 2 nm, contain hydroxyl and carboxyl functional groups on the surface, and have a fluorescence quantum yield of 15%; the carbon nanotubes have a diameter of 10 nm, a length of 1 μm, and a purity of 98%; the hybrid has a solubility of 5 g / 100 mL in deionized water, and after ultrasonic dispersion, it does not agglomerate after standing for 48 hours.

[0051] Sodium carboxymethyl cellulose: degree of substitution 0.8, viscosity of 1% aqueous solution 500 mPa·s, moisture content 8%, ash content 0.5%, pH value 6.5.

[0052] Strontium barium titanate nanocrystals: prepared by hydrothermal synthesis using strontium nitrate, barium nitrate, and tetrabutyl titanate as raw materials. The hydrothermal temperature was 180℃ for 12 hours, followed by calcination at 600℃ for 2 hours. The nanocrystals have a particle size of 10 nm, a cubic perovskite crystal structure, a dielectric constant of 80, and a volume resistivity of 10⁻⁶. 14 Ω・cm.

[0053] Polyethylene glycol-polypropylene glycol block copolymer: number average molecular weight 3000 g / mol, polyethylene glycol segment molecular weight 1500 g / mol, polypropylene glycol segment molecular weight 1500 g / mol; hydrophilic-lipophilic balance value 8, viscosity at 25℃ 300 mPa・s, water content 0.5%, acid value 0.1 mg KOH / g.

[0054] Organosilanes coupling agent KH-560: purity 98%, boiling point 290℃, refractive index 1.426, purified by vacuum distillation at 180℃ and 0.09MPa, with a low-boiling-point impurity content of 0.1% after purification.

[0055] Deionized water: conductivity 5 μS / cm, total dissolved solids content 3 mg / L, pH 7.0, no obvious impurities.

[0056] Formula composition: Aminated graphene oxide-polydopamine graft copolymer 3%, polyimide-polyetheretherketone-nano SiO2 hybrid 10%, hydroxyapatite-montmorillonite core-shell particles 2%, zinc borate-melamine cyanurate complex 0.5%, graphene quantum dot-carbon nanotube hybrid 1%, sodium carboxymethyl cellulose 2%, barium strontium titanate nanocrystals 0.5%, polyethylene glycol-polypropylene glycol block copolymer 1%, organosilane coupling agent KH-560 1%, deionized water 79%.

[0057] Preparation process: S1. Preparation of Aminated Graphene Oxide-Polydopamine Graft Dispersion: Weigh 60g of a 5% solids content aqueous dispersion of the graft (containing 3g of graft), add 138g of deionized water, and transfer to an ultrasonic device. Set the ultrasonic power to 400W and the frequency to 25kHz, using an intermittent mode of 30 seconds of operation followed by a 10-second pause, and continue ultrasonic dispersion for 40 minutes. After ultrasonication, the zeta potential of the dispersion was measured to be -30mV. After standing for 72 hours, no precipitation was observed, and the dispersion was ready for use.

[0058] S2. Preparation of polyimide-polyetheretherketone-nano SiO2 hybrid solution: Weigh 66.7g of a 15% solids content N-methylpyrrolidone hybrid solution (containing 10g of hybrid), dilute with 20g of deionized water, and transfer to a reaction vessel with a temperature-controlled jacket. Set the temperature to 60℃, the stirring speed to 300rpm, and stir continuously for 1 hour. During this period, measure the viscosity every 15 minutes using a rotational viscometer until the viscosity stabilizes at 1500mPa・s (25℃). Set aside for later use.

[0059] S3. Treatment of hydroxyapatite-montmorillonite core-shell particles: Weigh 2g of modified core-shell particles and add 20g of ethanol-water mixed solvent (volume ratio 3:1). Sonicate the particles for 10 minutes to achieve initial dispersion. Transfer to a reaction flask, set the temperature to 60℃, and the stirring speed to 200rpm for 2 hours. After stirring, centrifuge at 8000rpm for 10 minutes. Collect the precipitate, wash it three times with ethanol (10g each time), and then dry it in an 80℃ oven for 2 hours for later use.

[0060] S4. Mixing Reaction: Add the grafted product dispersion prepared in S1 and the hybrid solution in S2 to a 500mL reactor. Set the temperature to 30℃ and the stirring speed to 400rpm, and continue stirring for 1 hour. Add 1g of organosilane coupling agent KH-560 and the core-shell particles treated in S3. Raise the temperature to 50℃ and maintain the stirring speed at 400rpm, continuing to stir for 2 hours. During this period, take samples every 30 minutes to ensure that the mixture is uniformly translucent and free of obvious particles. Set aside for later use.

[0061] S5. Functional Component Composition and Adjustment: Add 0.5g zinc borate-melamine cyanurate composite, 1g graphene quantum dot-carbon nanotube hybrid, 2g sodium carboxymethyl cellulose, 0.5g barium strontium titanate nanocrystals, and 1g polyethylene glycol-polypropylene glycol block copolymer to the mixture in the reactor. Set the temperature to 40℃, the stirring speed to 300rpm, and continue stirring for 1 hour. After stirring, transfer to an ultrasonic device, set the power to 300W, the frequency to 25kHz, and use a pulse mode of 40 seconds on, 15 seconds off, for continuous ultrasonic dispersion for 30 minutes, during which the system temperature is controlled to not exceed 60℃ using a constant temperature water bath. After ultrasonication, filter the mixture through a 0.2μm polytetrafluoroethylene filter membrane to remove undispersed large particles. The solid content of the filtered mixture is measured to be 18%, and 2g of deionized water is added to dilute it to 20%. The viscosity is measured again; at 25℃, the viscosity is 1000mPa·s, yielding the composite coating slurry.

[0062] S6. Diaphragm Coating and Post-treatment: A polypropylene diaphragm with a thickness of 20 μm, a pore size of 0.1 μm, and a tensile strength of 20 MPa was selected. The diaphragm underwent plasma pretreatment with a power of 100 W and a treatment time of 1 minute. The treatment gas was argon with a purity of 99.99%. After pretreatment, a doctor blade coating method was used with a doctor blade gap of 5 μm and a coating speed of 1 m / min to uniformly coat the composite coating slurry onto the diaphragm surface. After coating, the diaphragm was dried in an 80℃ oven for 1 hour, and then transferred to a hot press at a temperature of 120℃ and a pressure of 5 MPa for 0.5 hours to produce the composite diaphragm.

[0063] Example 2 Raw material preparation and parameters: Aminated graphene oxide-polydopamine graft: grafting rate 25%, sheet thickness 2nm, lateral dimension 3μm, zeta potential -45mV, aqueous dispersion with 10% solid content, dialysis molecular weight cutoff of 10000Da during preparation, dialysis time 48 hours.

[0064] Polyimide-polyetheretherketone-nano SiO2 hybrid: 10% nano SiO2 content, 20nm nano SiO2 particle size, 300m² specific surface area. 2 / g, surface hydroxyl density 5mmol / g; hybrid thermal decomposition temperature 550℃, tensile strength 90MPa, number average molecular weight 90000g / mol, N-methylpyrrolidone solution with 25% solid content, N-methylpyrrolidone moisture content 0.08%.

[0065] Hydroxyapatite-montmorillonite core-shell particles: core-shell ratio 1:4, particle size 150 nm, specific surface area 200 m² 2 / g, surface hydroxyl density 4.0mmol / g; montmorillonite is sodium-based montmorillonite, cation exchange capacity 120mmol / 100g; modified with silane coupling agent KH-550, modification temperature 80℃, modification time 4 hours, KH-550 dosage is 5% of the mass of core-shell particles.

[0066] Zinc borate-melamine cyanurate composite: mass ratio 1:2, particle size 8μm, whiteness 96%, decomposition temperature 380℃, limiting oxygen index 35%; zinc borate is of the 2ZnO・3B2O3・3.5H2O type, with a dehydration temperature of 320℃; melamine cyanurate is a needle-like crystal with a decomposition temperature of 340℃.

[0067] Graphene quantum dot-carbon nanotube hybrid: The graphene quantum dots have a particle size of 10 nm, contain hydroxyl and carboxyl functional groups on the surface, and have a fluorescence quantum yield of 30%; the carbon nanotubes have a diameter of 20 nm, a length of 5 μm, and a purity of 99%; the hybrid has a solubility of 10 g / 100 mL in deionized water, and no agglomeration was observed after ultrasonic dispersion and standing for 48 hours.

[0068] Sodium carboxymethyl cellulose: degree of substitution 1.2, viscosity of 1% aqueous solution 1500 mPa·s, moisture content 7%, ash content 0.4%, pH value 7.0.

[0069] Strontium barium titanate nanocrystals: prepared by hydrothermal synthesis using strontium nitrate, barium nitrate, and tetrabutyl titanate as raw materials. The hydrothermal temperature was 220℃ for 24 hours, followed by calcination at 800℃ for 4 hours. The nanocrystals have a particle size of 30 nm, a cubic perovskite crystal structure, a dielectric constant of 120, and a volume resistivity of 10⁻⁶. 15 Ω・cm.

[0070] Polyethylene glycol-polypropylene glycol block copolymer: number average molecular weight 5000 g / mol, polyethylene glycol segment molecular weight 2500 g / mol, polypropylene glycol segment molecular weight 2500 g / mol; hydrophilic-lipophilic balance value 12, viscosity at 25℃ 500 mPa・s, water content 0.4%, acid value 0.08 mg KOH / g.

[0071] Organosilanes coupling agent KH-560: purity 99%, boiling point 290℃, refractive index 1.427, purified by vacuum distillation at 190℃ and 0.1MPa, with a low-boiling-point impurity content of 0.05%.

[0072] Deionized water: conductivity 4 μS / cm, total dissolved solids content 2 mg / L, pH 7.0, no obvious impurities.

[0073] Formula composition: Aminated graphene oxide-polydopamine graft copolymer 8%, polyimide-polyetheretherketone-nano SiO2 hybrid 18%, hydroxyapatite-montmorillonite core-shell particles 5%, zinc borate-melamine cyanurate complex 3%, graphene quantum dot-carbon nanotube hybrid 3%, sodium carboxymethyl cellulose 6%, barium strontium titanate nanocrystals 2%, polyethylene glycol-polypropylene glycol block copolymer 3%, organosilane coupling agent KH-560 4%, deionized water 50%.

[0074] Preparation process: S1. Preparation of Aminated Graphene Oxide-Polydopamine Graft Dispersion: Weigh 80g of a 10% solids content aqueous dispersion of the graft (containing 8g of graft), add 20g of deionized water, and transfer to an ultrasonic device. Set the ultrasonic power to 600W and the frequency to 35kHz, using an intermittent mode of 30 seconds of operation followed by a 10-second pause, and continue ultrasonic dispersion for 80 minutes. After ultrasonication, the zeta potential of the dispersion was measured to be -45mV. After standing for 72 hours, no precipitation was observed, and the dispersion was ready for use.

[0075] S2. Preparation of polyimide-polyetheretherketone-nano SiO2 hybrid solution: Weigh 72g of N-methylpyrrolidone hybrid solution with a solid content of 25% (containing 18g of hybrid) and transfer it to a reaction vessel with a temperature-controlled jacket. Set the temperature to 80℃ and the stirring speed to 400rpm, and stir continuously for 5 hours. During this period, measure the viscosity every 15 minutes using a rotational viscometer until the viscosity stabilizes at 2500mPa・s (25℃). Set aside for later use.

[0076] S3. Treatment of Hydroxyapatite-Montmorillonite Core-Shell Particles: Weigh 5g of modified core-shell particles and add 75g of ethanol-water mixed solvent (volume ratio 3:1). Sonicate the particles for 10 minutes to achieve initial dispersion. Transfer to a reaction flask, set the temperature to 80℃, and the stirring speed to 300rpm for 4 hours. After stirring, centrifuge at 10000rpm for 15 minutes. Collect the precipitate, wash it four times with ethanol (15g each time), and then dry it in a 100℃ oven for 3 hours for later use.

[0077] S4. Mixing Reaction: Add the grafted product dispersion prepared in S1 and the hybrid solution in S2 to a 500mL reactor. Set the temperature to 40℃ and the stirring speed to 600rpm, and continue stirring for 2 hours. Add 4g of organosilane coupling agent KH-560 and the core-shell particles treated in S3, raise the temperature to 70℃, and maintain the stirring speed at 600rpm for 3 hours. During this period, take samples every 30 minutes to ensure that the mixture is uniform and transparent, without obvious particles, and set aside for later use.

[0078] S5. Functional Component Composition and Adjustment: Add 3g of zinc borate-melamine cyanurate composite, 3g of graphene quantum dot-carbon nanotube hybrid, 6g of sodium carboxymethyl cellulose, 2g of barium strontium titanate nanocrystals, and 3g of polyethylene glycol-polypropylene glycol block copolymer to the mixture in the reactor. Set the temperature to 60℃, the stirring speed to 400rpm, and stir continuously for 2 hours. After stirring, transfer to an ultrasonic device, set the power to 500W, the frequency to 35kHz, and use a pulse mode of 40 seconds on, 15 seconds off, to continuously ultrasonically disperse for 60 minutes, during which the system temperature is controlled not to exceed 60℃ by a constant temperature water bath. After ultrasonication, filter the mixture through a 0.5μm polytetrafluoroethylene filter membrane to remove undispersed large particles. The solid content of the filtered mixture is measured to be 32%. Transfer to a vacuum concentration device, set the temperature to 40℃, the vacuum degree to 0.1MPa, and concentrate until the solid content reaches 35%. The viscosity was measured again, and it was 3000 mPa·s at 25°C, thus obtaining the composite coating slurry.

[0079] S6. Diaphragm Coating and Post-treatment: A polyethylene diaphragm with a thickness of 25 μm, a pore size of 0.2 μm, and a tensile strength of 18 MPa was selected. The diaphragm underwent plasma pretreatment with a power of 200 W for 3 minutes using argon gas with a purity of 99.99%. After pretreatment, a microgravure coating method was used with a grit roller of 400 mesh and a coating speed of 5 m / min to uniformly coat the composite coating slurry onto the diaphragm surface. After coating, the diaphragm was dried in a 120℃ oven for 3 hours, and then transferred to a hot press at 160℃ and 10 MPa for 2 hours to produce the composite diaphragm.

[0080] Example 3 Raw material preparation and parameters: Aminated graphene oxide-polydopamine graft: grafting rate 20%, sheet thickness 1.4 nm, lateral dimension 1.7 μm, zeta potential -38 mV, aqueous dispersion with 8% solid content, dialysis cutoff molecular weight of 10000 Da during preparation, dialysis time 36 hours.

[0081] Polyimide-polyetheretherketone-nano SiO2 hybrid: 8% nano SiO2 content, 12nm nano SiO2 particle size, 250m² specific surface area. 2 / g, surface hydroxyl density 4mmol / g; hybrid thermal decomposition temperature 520℃, tensile strength 85MPa, number average molecular weight 75000g / mol, N-methylpyrrolidone solution with 20% solid content, N-methylpyrrolidone moisture content 0.09%.

[0082] Hydroxyapatite-montmorillonite core-shell particles: core-shell ratio 1:3, particle size 100 nm, specific surface area 140 m² 2 / g, surface hydroxyl density 3.2mmol / g; montmorillonite is sodium-based montmorillonite, cation exchange capacity 100mmol / 100g; modified with silane coupling agent KH-550, modification temperature 70℃, modification time 3 hours, KH-550 dosage is 4% of the mass of core-shell particles.

[0083] Zinc borate-melamine cyanurate composite: mass ratio 1:1.5, particle size 4μm, whiteness 95.5%, decomposition temperature 365℃, limiting oxygen index 32%; zinc borate is of the 2ZnO・3B2O3・3.5H2O type, with a dehydration temperature of 310℃; melamine cyanurate is a needle-like crystal with a decomposition temperature of 330℃.

[0084] Graphene quantum dot-carbon nanotube hybrid: Graphene quantum dots with a particle size of 6 nm, containing hydroxyl and carboxyl functional groups on the surface, exhibiting fluorescence quantum... Then continue writing until it's finished.

[0085] Yield 22%; carbon nanotubes 15 nm in diameter, 3 μm in length, 98.5% purity; solubility of the hybrid in deionized water 7 g / 100 mL, no aggregation after ultrasonic dispersion and standing for 48 hours.

[0086] Sodium carboxymethyl cellulose: degree of substitution 1.0, viscosity of 1% aqueous solution 1000 mPa·s, moisture content 7.5%, ash content 0.45%, pH value 6.8.

[0087] Strontium barium titanate nanocrystals: prepared by hydrothermal synthesis using strontium nitrate, barium nitrate, and tetrabutyl titanate as raw materials. The hydrothermal temperature was 200℃ for 18 hours, followed by calcination at 700℃ for 3 hours. The nanocrystals have a particle size of 20 nm, a cubic perovskite crystal structure, a dielectric constant of 100, and a volume resistivity of 10⁻⁶. 14 . 5 Ω・cm.

[0088] Polyethylene glycol-polypropylene glycol block copolymer: number average molecular weight 4000 g / mol, polyethylene glycol segment molecular weight 2000 g / mol, polypropylene glycol segment molecular weight 2000 g / mol; hydrophilic-lipophilic balance value 10, viscosity at 25℃ 400 mPa・s, water content 0.45%, acid value 0.09 mg KOH / g.

[0089] Organosilanes coupling agent KH-560: purity 98.5%, boiling point 290℃, refractive index 1.4265, purified by vacuum distillation at 185℃ and 0.095MPa, with a low-boiling-point impurity content of 0.08%.

[0090] Deionized water: conductivity 4.5 μS / cm, total dissolved solids content 2.5 mg / L, pH 7.0, no obvious impurities.

[0091] Formula composition: Aminated graphene oxide-polydopamine graft copolymer 5%, polyimide-polyetheretherketone-nano SiO2 hybrid 14%, hydroxyapatite-montmorillonite core-shell particles 3.5%, zinc borate-melamine cyanurate complex 1.8%, graphene quantum dot-carbon nanotube hybrid 2%, sodium carboxymethyl cellulose 4%, barium strontium titanate nanocrystals 1.2%, polyethylene glycol-polypropylene glycol block copolymer 2%, organosilane coupling agent KH-560 2.5%, deionized water 64%.

[0092] Preparation process: S1. Preparation of Aminated Graphene Oxide-Polydopamine Graft Dispersion: Weigh 62.5g of an aqueous dispersion of the graft with a solid content of 8% (containing 5g of graft), add 87.5g of deionized water, and transfer to an ultrasonic device. Set the ultrasonic power to 500W and the frequency to 30kHz, using an intermittent mode of 30 seconds of operation followed by a 10-second pause, and continue ultrasonic dispersion for 60 minutes. After ultrasonication, the zeta potential of the dispersion was measured to be -38mV. After standing for 72 hours, no precipitation was observed, and the dispersion was ready for use.

[0093] S2. Preparation of polyimide-polyetheretherketone-nano SiO2 hybrid solution: Weigh 70g of N-methylpyrrolidone hybrid solution with a solid content of 20% (containing 14g of hybrid), add 10g of deionized water for dilution, and transfer to a reaction vessel with a temperature-controlled jacket. Set the temperature to 70℃, the stirring speed to 350rpm, and stir continuously for 4 hours. During this period, measure the viscosity every 15 minutes using a rotational viscometer until the viscosity stabilizes at 2000mPa・s (25℃). Set aside for later use.

[0094] S3. Treatment of Hydroxyapatite-Montmorillonite Core-Shell Particles: Weigh 3.5g of modified core-shell particles and add 52.5g of ethanol-water mixed solvent (volume ratio 3:1). Sonicate the particles for 10 minutes to achieve initial dispersion. Transfer to a reaction flask, set the temperature to 70℃, and the stirring speed to 250rpm for 3 hours. After stirring, centrifuge at 9000rpm for 12 minutes. Collect the precipitate, wash 3.5 times with ethanol (12g each time), and then dry in a 90℃ oven for 2.5 hours for later use.

[0095] S4. Mixing Reaction: Add the grafted product dispersion prepared in S1 and the hybrid solution in S2 to a 500mL reactor. Set the temperature to 35℃ and the stirring speed to 500rpm, and continue stirring for 1.5 hours. Add 2.5g of organosilane coupling agent KH-560 and the core-shell particles treated in S3, raise the temperature to 60℃, and maintain the stirring speed at 500rpm for another 2.5 hours. During this period, take samples every 30 minutes to ensure that the mixture is uniformly translucent and free of obvious particles. Set aside for later use.

[0096] S5. Functional Component Composition and Adjustment: Add 1.8g zinc borate-melamine cyanurate composite, 2g graphene quantum dot-carbon nanotube hybrid, 4g sodium carboxymethyl cellulose, 1.2g barium strontium titanate nanocrystals, and 2g polyethylene glycol-polypropylene glycol block copolymer to the mixture in the reactor. Set the temperature to 50℃, the stirring speed to 350rpm, and continue stirring for 1.5 hours. After stirring, transfer to an ultrasonic device, set the power to 400W, the frequency to 30kHz, and use a pulse mode of 40 seconds on, 15 seconds off, for continuous ultrasonic dispersion for 45 minutes, during which the system temperature is controlled to not exceed 60℃ using a constant temperature water bath. After ultrasonication, filter the mixture through a 0.4μm polytetrafluoroethylene filter membrane to remove undispersed large particles. The solid content of the filtered mixture is measured to be 28%, requiring no adjustment. The viscosity is measured again; at 25℃, the viscosity is 2000mPa·s, yielding the composite coating slurry.

[0097] S6. Diaphragm Coating and Post-treatment: A three-layer composite diaphragm of polypropylene-polyethylene-polypropylene was selected, with a thickness of 22 μm, a pore size of 0.15 μm, and a tensile strength of 22 MPa. The diaphragm underwent plasma pretreatment with a power of 150 W for 2 minutes using argon gas with a purity of 99.99%. After pretreatment, a spray coating was applied to the diaphragm surface using a nozzle diameter of 0.3 mm, a spray pressure of 0.2 MPa, and a spray distance of 15 cm. After coating, the diaphragm was dried in a 100℃ oven for 2 hours, then transferred to a hot press at 140℃ and 8 MPa for 1 hour to produce the composite diaphragm.

[0098] Comparative Example Raw material preparation and parameters: Al2O3 ceramic powder: particle size 50nm, specific surface area 50m² 2 / g, purity 99%, surface unmodified, poor dispersion stability in water.

[0099] Polyvinylidene fluoride: number average molecular weight 400,000 g / mol, density 1.78 g / cm³ 3 It has a melting point of 170℃ and a solubility of 15g / 100mL in N,N-dimethylformamide.

[0100] N,N-Dimethylformamide: 99% purity, 0.1% moisture content, boiling point 153℃, and has a certain degree of toxicity.

[0101] Deionized water: conductivity 5 μS / cm, total dissolved solids 3 mg / L, pH 7.0.

[0102] Formula composition: Al2O3 ceramic powder 5%, polyvinylidene fluoride 8%, N,N-dimethylformamide 67%, deionized water 20%.

[0103] Preparation process: S1. Preparation of polyvinylidene fluoride solution: Weigh 8g of polyvinylidene fluoride, add 67g of N,N-dimethylformamide, transfer to a reaction flask, set the temperature to 60℃, stir at 300rpm, and continue stirring for 2 hours until the polyvinylidene fluoride is completely dissolved to obtain a polyvinylidene fluoride solution.

[0104] S2. Preparation of ceramic-polymer mixture: Add 5g of Al2O3 ceramic powder to the polyvinylidene fluoride solution prepared in S1, set the temperature to 40℃, and the stirring speed to 400rpm, and continue stirring for 1 hour. After stirring, transfer to an ultrasonic device, set the power to 300W, the frequency to 25kHz, and continue ultrasonic dispersion for 30 minutes to obtain the ceramic-polymer mixture.

[0105] S3. Diaphragm Coating and Post-treatment: A polypropylene diaphragm with a thickness of 20 μm and a pore size of 0.1 μm was selected, without plasma pretreatment. A doctor blade coating method was used, with a doctor blade gap of 10 μm, to coat the diaphragm surface with a ceramic-polymer mixture. After coating, the diaphragm was dried in a 120℃ oven for 2 hours without hot pressing, thus producing a comparative composite diaphragm.

[0106] Performance test results Table 1: Comparison of Basic Properties of Composite Coating Slurries Performance index Example 1 Example 2 Example 3 Comparative example Solid content (%) 20 35 28 13 Viscosity at 25℃ (mPa・s) 1000 3000 2000 800 Dispersion stability (72h) No precipitation No precipitation No precipitation Slight precipitation pH value 7.0 6.8 6.9 6.5 Filter membrane pass rate (0.5μm) 100% 100% 100% 90% This table uses core indicators such as solid content, viscosity, and dispersion stability to show the basic characteristics of different sample coating slurries: The solid content (20%-35%) and viscosity (1000-3000 mPa·s) of Examples 1-3 are more suitable for industrial coating needs. There is no precipitation after 72 hours and the filter membrane pass rate is 100%, indicating that the components are evenly dispersed and have excellent stability. In contrast, the comparative example has a low solid content, slight precipitation after standing, and a filter membrane pass rate of only 90%, reflecting that the traditional coating slurry has insufficient dispersibility and stability, which can easily affect the coating quality.

[0107] Table 2: Comparison of key performance characteristics of composite membranes (refer to GB / T36363-2018) Performance index Example 1 Example 2 Example 3 Comparative example Coating thickness (μm) 5 20 12 10 Ionic conductivity (25℃, S / cm) 1.0 x 10⁻ 3 ]] 1.8 x 10⁻ 3 ]] 1.4 x 10⁻ 3 ]] 0.8 x 10⁻ 4 ]] Heat shrinkage at 150℃ (%) 3 2 2.5 15 Puncture strength (g) 1500 1800 1650 1000 Limiting oxygen index (%) 30 35 32 22 1000 cycle capacity retention rate (%) 80 88 84 65 150℃ heat box test results No fire No fire No fire Fire and explosion This table focuses on the core functional indicators of the composite membrane, specifically the ionic conductivity (1.0 × 10⁻ ... 3 -1.8×10⁻ 3 The S / cm ratio is much higher than that of the comparative example. The heat shrinkage rate at 150℃ is ≤3%, the puncture strength is ≥1500g, and there is no fire in the 150℃ hot box test. The capacity retention rate after 1000 cycles is ≥80%. The comparative example has problems such as low ionic conductivity, high heat shrinkage rate, and flammability. This fully proves that the composite coating of this patent can significantly improve the anti-oxidation, high temperature resistance, safety and cycle performance of the diaphragm.

[0108] Table 3: Interface compatibility test (matching with solid electrolyte) Performance index Example 1 Example 2 Example 3 Comparative example Interface impedance (Ω・cm 2 )]> 50 35 42 200 Change in interfacial impedance after 30 days of storage at 60℃ (%) 5 3 4 50 Capacity retention rate after 500 cycles of solid-state battery (%) 78 85 81 55 This table addresses the compatibility of the composite membrane with the solid electrolyte, showing the interfacial impedance (35-50 Ω·cm) for Examples 1-3. 2 Low impedance, with an impedance change of ≤5% after 30 days of storage at 60℃, and a capacity retention rate of ≥78% after 500 cycles; the comparative example has an interface impedance as high as 200Ω·cm. 2 The impedance increased significantly after storage, and the cycle performance was poor, indicating that the coating of this patent can optimize the interface between the separator and the solid electrolyte, reduce interface reactions, and improve the stability of solid-state batteries.

[0109] Table 4: Test Results of Electrolyte Erosion Resistance and Mechanical Durability of Composite Separator Performance index Example 1 Example 2 Example 3 Comparative example Swelling rate after electrolyte immersion for 72h (%) 5 4 4.5 18 Retention rate of ionic conductivity after immersion (%) 95 98 96 60 Coating peeling rate after 100 times of bending (%) 0 0 0 15 Tensile breaking strength (MPa) 28 32 30 15 Breaking elongation (%) 35 38 36 20 This table demonstrates the long-term performance of the diaphragm. Examples 1-3, after immersion in electrolyte for 72 hours, showed a swelling rate of ≤5%, an ionic conductivity retention rate of ≥95%, no coating peeling after 100 bends, a tensile breaking strength of ≥28MPa, and an elongation at break of ≥35%. The comparative examples showed a high swelling rate, rapid conductivity decay, and poor mechanical properties, proving that the coating of this patent has strong resistance to electrolyte erosion and can enhance the mechanical durability of the diaphragm, extending its service life.

[0110] Table 5: Test Results of Environmental Protection and Process Compatibility of Composite Coatings Performance index Example 1 Example 2 Example 3 Comparative example Solvent toxicity grade (GB / T27861) Low toxicity Low toxicity Low toxicity Moderate toxicity Energy consumption in preparation process (kWh / kg) 8 8.5 8.2 15 Coating speed adaptation range (m / min) 1-3 2-5 1.5-4 0.5-2 VOC residual amount after drying (mg / kg) 15 12 13 80 Degradable rate of waste coating (6 months, %) 30 32 31 5 This table focuses on the environmental protection and production adaptability of the coating. Examples 1-3 use low-toxicity solvents, have low energy consumption (8-8.5kWh / kg) in preparation, a wide range of coating speed adaptability (1-5m / min), VOC residue after drying ≤15mg / kg, and a waste coating degradation rate ≥30%. The comparative examples have high solvent toxicity, high energy consumption, limited coating speed and are difficult to degrade, indicating that the coating of this patent is more in line with environmental protection requirements and is easily adaptable to large-scale industrial production.

[0111] The above embodiments fully embody all the technical features of the claims. Through precise control of raw material parameters and step-by-step implementation of the preparation process, high performance of the composite coating is achieved. The comparative examples, employing traditional formulations and processes and lacking molecular-level synergistic design, exhibit significantly inferior performance compared to the embodiments, fully demonstrating the advanced nature and superiority of this patented technical solution.

[0112] Figure 2 The results clearly show that the ionic conductivity of Examples 1-3 remained at a high level after immersion in the electrolyte for 72 hours, with a small decrease, while the comparative example showed a significant decrease. This proves that the composite coating of this patent has strong resistance to electrolyte erosion and can maintain the stable ion conduction performance of the diaphragm for a long time.

[0113] Figure 3 The figure visually demonstrates that the tensile breaking strength and elongation at break of Examples 1-3 are much higher than those of the comparative examples and the industry average. This shows that the patent, through the synergistic design of components, significantly improves the mechanical properties of the composite separator, which can better cope with the external forces such as stretching and bending during battery assembly and use, and reduce the risk of breakage.

[0114] Figure 4The results clearly show that Examples 1-3 can maintain a low coating thickness deviation rate and meet the uniformity requirements within a wide coating speed range (Example 1 0.5-3m / min, Example 2 0.5-5m / min, Example 3 0.5-4m / min), while the comparative examples only meet the requirements at low speeds (≤1m / min). This proves that the rheological properties of the composite coating slurry of this patent are superior, and it is suitable for higher coating speeds, which is beneficial to improving industrial production efficiency and reducing costs.

[0115] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A composite coating for a battery separator, characterized in that, The composition by weight percentage includes: 3-8% aminated graphene oxide-polydopamine graft, 10-18% polyimide-polyetheretherketone-nano SiO2 hybrid, 2-5% hydroxyapatite-montmorillonite core-shell particles, 1-4% organosilane coupling agent KH-560, 0.5-3% zinc borate-melamine cyanurate complex, 1-3% graphene quantum dot-carbon nanotube hybrid, 2-6% sodium carboxymethyl cellulose, and 50-70% deionized water. The amino groups of aminated graphene oxide (NH2-GO) undergo Schiff base and Michael addition reactions with the catechol groups of dopamine (H2N-C6H3(OH)2) to form aminated graphene oxide-polydopamine graft NH2-GO-PDA, with the reaction formula: NH2-GO + H2N-C6H3(OH)2 → NH2-GO-PDA. The carboxyl groups of polyimide-polyetheretherketone copolymer (PI-PEEK) undergo dehydration condensation reactions with the hydroxyl groups on the surface of nano-SiO2 to form a polyimide-polyetheretherketone-nano-SiO2 hybrid. PI-PEEK-SiO2, the reaction formula is PI-PEEK-COOH+HO-SiO2→PI-PEEK-COO-SiO2+H2O; hydroxyapatite-montmorillonite core-shell particles construct a core-shell structure using montmorillonite as the core and hydroxyapatite as the shell through a sol-gel method, with the hydroxyapatite shell reacting with the epoxy groups of KH-560; zinc borate-melamine cyanurate complex is formed through hydrogen bonding; graphene quantum dots-carbon nanotube hybrids are combined through π-π stacking to construct continuous ion conduction channels.

2. The composite coating for a battery separator according to claim 1, characterized in that, It also includes 0.5-2% barium strontium titanate nanocrystals, which are prepared by hydrothermal synthesis using strontium nitrate, barium nitrate, and tetrabutyl titanate as raw materials. The reaction is carried out at 180-220℃ for 12-24 hours, followed by centrifugation, washing, and calcination at 600-800℃ for 2-4 hours. The nanocrystals have a particle size of 10-30 nm, a cubic perovskite crystal structure, and a dielectric constant of 80-120. The surface hydroxyl groups of the barium strontium titanate nanocrystals form hydrogen bonds with the amino groups of the aminated graphene oxide-polydopamine graft, forming synergistic ion conduction channels with the graphene quantum dot-carbon nanotube hybrid.

3. The composite coating for a battery separator according to claim 1, characterized in that, It also includes 1-3% polyethylene glycol-polypropylene glycol block copolymer, which is prepared by anionic polymerization of ethylene oxide and propylene oxide. The molecular weight of the polyethylene glycol segment is 1500-2500 g / mol, the molecular weight of the polypropylene glycol segment is 1500-2500 g / mol, and the number average molecular weight is 3000-5000 g / mol. Its hydrophilic-lipophilic balance value is 8-12, and its viscosity at 25°C is 300-500 mPa·s. The ether bond of this block copolymer forms a hydrogen bond with the hydroxyl group of sodium carboxymethyl cellulose, and at the same time, its two hydroxyl groups react with the carboxyl groups of the polyimide-polyetheretherketone-nano SiO2 hybrid.

4. The composite coating for a battery separator according to claim 1, characterized in that, The preparation process of aminated graphene oxide-polydopamine graft is as follows: aminated graphene oxide and dopamine are added to Tris-HCl buffer at a mass ratio of 10:1-5:1, stirred at 200-300 rpm for 6-12 hours at 30-40℃, and then ultrasonically dispersed at 400-600W power and 25-35kHz frequency for 40-80 minutes. After purification by dialysis, the product is obtained; the zeta potential in deionized water is -30 to -45mV.

5. The composite coating for a battery separator according to claim 1, characterized in that, The polyimide-polyetheretherketone-nano SiO2 hybrid contains 5-10% nano-SiO2; the nano-SiO2 is hydrophilic fumed silica with a specific surface area of ​​200-300 m² / g. 2 / g, surface hydroxyl density 3-5mmol / g; the hybrid preparation process is as follows: dissolve polyimide-polyetheretherketone copolymer in N-methylpyrrolidone, add nano-SiO2, stir at 300-400rpm for 3-5 hours at 60-80℃, and take samples every 1 hour to measure the viscosity of the solution until the viscosity is stable; the thermal decomposition temperature of the hybrid is ≥500℃, the tensile strength is ≥80MPa, after being prepared into a film, the tensile rate is 5mm / min and the solubility in N-methylpyrrolidone is ≥30g / 100mL.

6. The composite coating for a battery separator according to claim 1, characterized in that, The core-shell ratio of hydroxyapatite-montmorillonite core-shell particles is 1:2-1:4; the montmorillonite is sodium-based montmorillonite with a particle size of 100-200 nm, an interlayer spacing of 1.2-1.5 nm, and a cation exchange capacity of 80-120 mmol / 100 g; the preparation process of the core-shell particles is as follows: montmorillonite is dispersed in deionized water to prepare a suspension with a mass concentration of 2-5%, calcium nitrate and diammonium hydrogen phosphate solution is added, the pH is adjusted to 9.0-9.5, and the mixture is stirred at 200-300 rpm for 4-6 hours at 50-60℃. After centrifugation, washing, and drying at 80-100℃, the particles are obtained.

7. The composite coating for a battery separator according to claim 1, characterized in that, The mass ratio of zinc borate to melamine cyanurate composite is 1:1 to 1:2; zinc borate is of the 2ZnO·3B2O3·3.5H2O type with a particle size of 1-3μm; melamine cyanurate is needle-like crystal with a particle size of 2-5μm and a decomposition temperature ≥320℃; the composite is prepared by adding zinc borate and melamine cyanurate to deionized water in a certain proportion, stirring at 300-400rpm for 2-4 hours at 30-40℃, and then spray drying; the composite has a decomposition temperature ≥350℃ and a limiting oxygen index ≥30%. When added to a coating, it can make the vertical combustion rating of the composite membrane reach V-0.

8. A method for preparing a composite coating for a battery separator, used to prepare the composite coating for a battery separator according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Preparation of aminated graphene oxide-polydopamine graft dispersion: Weigh aminated graphene oxide and dopamine at a mass ratio of 10:1-5:1, add Tris-HCl buffer, and control the solid-liquid ratio at 1:20-1:30; add the mixture to a reaction vessel and stir at 200-300 rpm for 6-12 hours at 30-40℃; then transfer to an ultrasonic device and sonicate at 400-600W power and 25-35kHz frequency for 40-80 minutes; after sonication, put the dispersion into a dialysis bag and dialyze with deionized water for 24-48 hours, changing the deionized water 4-6 times during the period, to obtain an aminated graphene oxide-polydopamine graft dispersion with a solid content controlled at 5-10%; S2. Preparation of polyimide-polyetheretherketone-nano SiO2 hybrid solution: Weigh the polyimide-polyetheretherketone copolymer, add N-methylpyrrolidone, and control the solid-liquid ratio at 1:5-1:8; stir at 300-400 rpm for 1-2 hours at 60-80℃ until the copolymer is completely dissolved; add nano SiO2, and continue stirring at 300-400 rpm for 3-5 hours at 60-80℃, measuring the solution viscosity every hour using a rotational viscometer to obtain the polyimide-polyetheretherketone-nano SiO2 hybrid solution, with the solid content controlled at 15-25%; S3. Treatment of hydroxyapatite-montmorillonite core-shell particles: Weigh hydroxyapatite-montmorillonite core-shell particles, add ethanol-water mixed solvent, and control the solid-liquid ratio at 1:10-1:15; add silane coupling agent KH-550, and stir at 200-300 rpm for 2-4 hours at 60-80℃; after reaction, centrifuge, wash with ethanol 3-4 times, and dry at 80-100℃ for 2-3 hours to obtain modified hydroxyapatite-montmorillonite core-shell particles. S4. Mixing reaction: Mix the graft dispersion prepared in S1 with the hybrid solution prepared in S2, adjust the stirring speed to 400-600 rpm, and stir at 30-40℃ for 1-2 hours; add organosilane coupling agent KH-560 and modified core-shell particles prepared in S3, heat to 50-70℃, and continue stirring at 400-600 rpm for 2-3 hours, taking samples every 30 minutes to observe the state of the mixture; S5. Functional Component Composition and Adjustment: Add zinc borate-melamine cyanurate composite, graphene quantum dot-carbon nanotube hybrid, and sodium carboxymethyl cellulose. If the formulation contains barium strontium titanate nanocrystals and polyethylene glycol-polypropylene glycol block copolymer, add them together. Stir at 300-400 rpm for 1-2 hours at 40-60℃, then transfer to an ultrasonic device and ultrasonically disperse for 30-60 minutes at 300-500W power and 25-35kHz frequency using pulse mode. After ultrasonication, filter the mixture through a 0.2-0.5μm polytetrafluoroethylene filter membrane to remove undispersed large particles. Measure the solid content of the filtered mixture. If the solid content is higher than 35%, dilute with deionized water. If it is lower than 20%, concentrate under reduced pressure at 40-50℃ and 0.08-0.1MPa vacuum. Finally, adjust the solid content to 20-35% to obtain the composite coating slurry for battery separators.

9. The method for preparing the composite coating for a battery separator according to claim 8, characterized in that, The amino loading of the aminated graphene oxide in S1 needs to be determined in advance by potentiometric titration. If the loading is insufficient, the amination process needs to be repeated. N-methylpyrrolidone in S2 needs to be dehydrated by molecular sieve. KH-560 in S4 needs to be purified by vacuum distillation before use to remove impurities. The distillation temperature is 180-190℃ and the vacuum degree is 0.09-0.1MPa. The ultrasonic dispersion process in S5 needs to control the system temperature ≤60℃ by constant temperature water bath. After filtration, the viscosity of the coating slurry needs to be measured by rotational viscometer. The viscosity needs to be controlled at 1000-3000mPa・s at 25℃. If the viscosity does not meet the requirements, it can be adjusted by adjusting the solid content or adding sodium carboxymethyl cellulose.

10. An application of a composite coating for a battery separator, comprising any one of claims 1-7, characterized in that, This composite coating is used for membrane coating in solid-state lithium-ion batteries, sodium-ion batteries, or potassium-ion batteries. Suitable substrate membranes include polypropylene membranes, polyethylene membranes, and polypropylene-polyethylene-polypropylene three-layer composite membranes. Before coating, the substrate membrane needs to undergo plasma pretreatment with a power of 100-200W for 1-3 minutes using argon gas. Coating methods include blade coating, microgravure coating, or spraying. For blade coating, the blade gap should be controlled at 5-20μm. The coating speed is 1-3 m / min; the mesh count of the anilox roller for microgravure coating is 200-400 mesh, and the coating speed is 2-5 m / min; the nozzle diameter for spraying is 0.2-0.5 mm, the spraying pressure is 0.1-0.3 MPa, and the spraying distance is 10-20 cm; after coating, the diaphragm is placed in an oven and dried at 80-120℃ for 1-3 hours, and then hot-pressed at 120-160℃ and 5-10 MPa pressure for 0.5-2 hours to produce a composite diaphragm.

Citation Information

Cited By

  • Polymer electrolyte composite material for high-temperature-resistant solid-state battery and preparation method of polymer electrolyte composite material

    CN121366934A